Serotyping of Brunei pneumococcal clinical strains and the investigation of their capability to adhere and invade a brain endothelium model. (September 2017) - Rahman, Nurul Adhwa; Sharudin, Aishah; Diah, Suwarni; Muharram, Siti Hanna
Abstract: Introduction: Pneumococcal infections have caused morbidity and mortality globally. Streptococcus pneumoniae (pneumococci) are commensal bacteria that colonize the nasopharynx, asymptomatically. From there, pneumococci can spread in the lungs causing pneumonia and disseminate in the bloodstream causing bacteremia (sepsis) and reach the brain leading to meningitis. Endothelial cells are one of the most important components of the blood-brain barrier that separates the blood from the brain and plays the first protective role against pneumococcal entry. Thus this study aimed to investigate on the ability of non-meningitis pneumococcal clinical strains to adhere and invade a brain endothelium model. Methods: Two pneumococcal Brunei clinical strains were serotyped by multiplex PCR method using oligonucleotide sequences derived from Centers for Disease Control and Prevention. A validated immortalised mouse brain endothelial cell line (bEnd.3) was used as a brain endothelium model for the study of the pneumococcal breach of the blood-brain barrier using an adherence and invasion assay. Results: Both of the pneumococcal clinical strains were found to be serotype 19F, a common circulating serotype in Southeast Asia and globally and possess the ability to adhere and invade the brain endothelial cells. Conclusion: In addition, this is the first report on the serotype identification of pneumococci in Brunei Darussalam and their application on a brain endothelium model. Further studies are required to understand the virulence capabilities of the clinical strains. Highlights: Brunei pneumococcal clinical strains were found to be serotype 19F. The strains possess the ability to adhere and invade the brain endothelial cells. A brain endothelium model (bEnd.3) were validated and applied in this study.